2010
DOI: 10.1016/j.exphem.2010.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony of telomere length among hematopoietic cells

Abstract: Objective-Little is known about the relations of telomere lengths among leukocyte subsets and between leukocytes and cells up the hematopoietic hierarchy. This information is relevant, since telomere dynamics in granulocytes were postulated to mirror those of hematopoietic stem cells (HSCs).Subjects and Methods-We examined in newborns' cord blood (UCB) the relationships of telomere length in hematopoietic progenitor cells (HPCs) (CD34 + CD45 − ) with that in T lymphocytes and in granulocytes. In addition, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
140
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(144 citation statements)
references
References 32 publications
4
140
0
Order By: Relevance
“…Genetic studies have shown that the telomerase reverse transcriptase (TERT) gene, an enzyme that is fundamental for the accurate de novo synthesis of telomeric ends, is one of the few identified risk loci for pancreatic cancer (8) as well as other tumor types (21). There is evidence pointing to a strong correlation in telomere length across somatic tissues and suggesting that the variability across cell and tissue types is remarkably lower than the interindividual variability of LTL (22)(23)(24), and natural rates of telomere shortening with age appear to follow a pattern of remarkable synchrony across different somatic tissue types (25). These observations identify LTL as a good proxy for overall telomere length and therefore a possibly useful marker for cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies have shown that the telomerase reverse transcriptase (TERT) gene, an enzyme that is fundamental for the accurate de novo synthesis of telomeric ends, is one of the few identified risk loci for pancreatic cancer (8) as well as other tumor types (21). There is evidence pointing to a strong correlation in telomere length across somatic tissues and suggesting that the variability across cell and tissue types is remarkably lower than the interindividual variability of LTL (22)(23)(24), and natural rates of telomere shortening with age appear to follow a pattern of remarkable synchrony across different somatic tissue types (25). These observations identify LTL as a good proxy for overall telomere length and therefore a possibly useful marker for cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…Still, some cross-sectional studies report synchrony over different tissues. One study by Kimura et al [40], for example, reported significant correlations between TL of hematopoietic progenitor cells from newborn umbilical cord blood samples and TL from lymphocytes or granulocytes, with r´s ranging from r =.88 to r =.94 [40]. In a second phase of their study, they showed that correlation between granulocytes TL and leukocyte TL were high at birth (r =.98) and stayed strong different age groups (r = .98).…”
Section: Telomeres In Different Tissuesmentioning
confidence: 87%
“…In a second phase of their study, they showed that correlation between granulocytes TL and leukocyte TL were high at birth (r =.98) and stayed strong different age groups (r = .98). These results derived from cross-sectional data of a cohort with 24 subjects (age 22 to 34 years) and another cohort with 400 subjects (age 0 to 100 years) [40]. Some studies implied TL synchrony between different tissue samples across different stages of an organism´s development.…”
Section: Telomeres In Different Tissuesmentioning
confidence: 97%
See 1 more Smart Citation
“…Telomere length appears to be inherited [6][7][8][9] and is highly correlated across various tissues within an individual. 6,[10][11][12][13][14] By influencing the number of possible cell divisions, telomere length could partly determine the number of primordial follicles and thus a woman's overall reproductive potential.…”
mentioning
confidence: 99%